Angiocrine Signaling in Sinusoidal Health and Disease - Cooper, Shawna A.; Kostallari, Enis; Shah, Vijay H. (Seminars in Liver Disease, 2023)
Liver sinusoidal endothelial cells (LSECs) are key players in maintaining hepatic homeostasis. They also play crucial roles during liver injury by communicating with liver cell types as well as immune cells and promoting portal hypertension, fibrosis, and inflammation. Cutting-edge technology, such as single cell and spatial transcriptomics, have revealed the existence of distinct LSEC subpopulations with a clear zonation in the liver. The signals released by LSECs are commonly called “angiocrine signaling.” In this review, we summarize the role of angiocrine signaling in health and disease, including zonation in healthy liver, regeneration, fibrosis, portal hypertension, nonalcoholic fatty liver disease, alcohol-associated liver disease, aging, drug-induced liver injury, and ischemia/reperfusion, as well as potential therapeutic advances. In conclusion, sinusoidal endotheliopathy is recognized in liver disease and promising preclinical studies are paving the path toward LSEC-specific pharmacotherapies.
Keywords: angiocrine signaling; liver sinusoidal endothelial cells; liver health; liver disease; therapeutics